2019
DOI: 10.1002/adma.201903914
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Engineering in Low‐Dimensional Crystal‐Structural Materials via Seed Screening

Abstract: CuSbSe 2[15] solar cells were also rapidly developed with PCE over 4%. However, caused by asymmetric atom coordination, the LDCS materials exhibit significantly anisotropic carrier transport in different orientations (Figure 1a,b). Along the covalent bond direction (the chain and the layer directions of 1D and 2D materials, respectively), the overlapping electron clouds are beneficial to the carrier transport ( Figure 1c, right part). Whereas, the carriers have to undergo interchain or interlayer barriers when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
145
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(145 citation statements)
references
References 39 publications
0
145
0
Order By: Relevance
“…Nevertheless, to date there are limited studies on such interlayer optical and electronic responses. [254][255][256][257][258] Furthermore, the highly anisotropic electrical and optical properties in MMCs integrated with 0D (quantum dots) or 1D organic and/or inorganic and perovskite semiconductor materials could open up a new path for next-generation electronic applications. Overall, the very recent exciting achievements in the field of few-layer MMCs showed a great potential for their application in next-generation electronic, optoelectronic, and emerging nanophotonics, including valley electronics, solar cells, sensors, and nonlinear optical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to date there are limited studies on such interlayer optical and electronic responses. [254][255][256][257][258] Furthermore, the highly anisotropic electrical and optical properties in MMCs integrated with 0D (quantum dots) or 1D organic and/or inorganic and perovskite semiconductor materials could open up a new path for next-generation electronic applications. Overall, the very recent exciting achievements in the field of few-layer MMCs showed a great potential for their application in next-generation electronic, optoelectronic, and emerging nanophotonics, including valley electronics, solar cells, sensors, and nonlinear optical applications.…”
Section: Discussionmentioning
confidence: 99%
“…where I(hkl) and I0(hkl) are the diffraction peak intensities of (hkl) planes in the measured and standard XRD pattern of Sb2Se3 (JCPDS 15-0861), respectively. Large TC value of a diffraction peak indicates preferred orientation along this particular direction [26]. As can be seen from the figure, the mixed-Sb2Se3 sample shows the highest overall TC values for the (hkl, l≠0) planes and the lowest TC values for the (hk0) planes among all the samples, indicating the optimal growth orientation of the film.…”
Section: Resultsmentioning
confidence: 81%
“…All the samples demonstrate vertical orientations, as evidenced by the prominent diffraction peaks of (211) and (221). Texture coefficients (TC) of the diffraction peaks were calculated using the equation below to quantitatively investigate the orientation preference (Figure 4b) [26]: It is well known that film orientation plays as an essential role in the photovoltaic performance of Sb 2 Se 3 thin film solar cells. Reports have shown that transport of photogenerated carriers would be facilitated within the bulk film once the Sb 2 Se 3 grains are in vertical orientations, as the carriers could travel readily within the covalently bonded ribbons in this case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, antimony chalcogenide thin‐film solar cells, including Sb 2 Se 3 , Sb 2 S 3 , and Sb 2 (S,Se) 3 alloy, have been developed rapidly in recent years. Sb 2 Se 3 solar cells based on superstrate configuration have achieved over 7.6% efficiency by vapor transport deposition (VTD) and rapid thermal evaporation (RTE) method . Simultaneously, the record efficiency of 9.2% of substrate configuration Sb 2 Se 3 solar cells has been obtained by constructing a nanorod array via a closed‐space sublimation (CSS) method .…”
Section: Introductionmentioning
confidence: 99%